The ethnoregional component of the party-political landscape of Europe - Vladimir Y. Shveytzer (Научно-аналитический вестник Института Европы РАН)
The article examines the politics and ideology of parties that focus on the interests of a part of the population of important regional areas of modern Europe. Their range extends from the Scandinavian-Baltic region of the EU to the Mediterranean-Black Sea territories of the Old World, primarily in Italy and Spain. These regionals are also electorally felt in the Eastern European states and the Balkans, and influence political life in Germany, Belgium, Britain, and Ireland. Their activity focuses on the topics of reforming the national economic system, not excluding the problem of finding a «new sovereignty» within the framework of a possible change in the country concentration of the European Union. The author suggests a typologization of parties according to national, regional, confessional and linguistic characteristics. The differentiation of these parties by their respective groups and factions in the European Parliament is being considered. Special attention is paid to the programmatic formulation of current European issues in the European Free Alliance faction. An analysis of the activities of ethno-regionals in such countries as Italy, Britain, Finland, and Belgium is proposed. Separatist tendencies are especially felt in Catalonia and Northern Ireland. The conflicting nature of the relations between the ethno-regional elite and the European establishment is emphasized.